Optimal VWAP trading under noisy conditions - Humphery-Jenner, Mark L. (Journal of Banking & Finance, 2011)
This article proposes an empirically tractable way to incorporate intra-day noise into a VWAP trading rule. In volatile markets, news arrives unexpectedly and rapidly. This should influence a trader’s trading decisions. However, the literature has not incorporated such information into an algorithmic trading framework. Subsequently, this paper presents a Dynamic VWAP (DVWAP) framework that allows informed traders to utilize random news; and thus, improve trade-execution.